Development of a high-accuracy 500 kg mass comparator for improved weight calibration capability. (January 2017) - Sun, Jianxin; Ueki, Masaaki; Ueda, Kazunaga
Highlights: A high-accuracy 500 kg mass comparator with 0.01 g readability has been developed. It adopted an electronic balance and a two-stage lever system with knife-edges. It reduced calibration uncertainties of large weights by 34–45%. Abstract: A high-accuracy 500 kg mass comparator with a readability of 0.01 g has been developed at the NMIJ/AIST in order to improve calibration capabilities for large weights from 100 kg to 500 kg. This newly developed mass comparator uses a high-accuracy electronic balance as the sensor and a high-sensitivity two-stage lever system with knife-edges to expand the maximum weighing capacity. This design made it possible to reduce the calibration uncertainties of large weights by 34–45%. This paper reports the basic design of the mass comparator and the improved results for large weight calibrations at the NMIJ.